2015
DOI: 10.1089/jmf.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lutein Modulates Growth and Survival Genes in Prostate Cancer Cells

Abstract: Lutein is a carotenoid pigment present in fruits and vegetables that has anti-inflammatory and antitumor properties. In this study, we examined the effect of lutein on proliferation and survival-associated genes in prostate cancer (PC-3) cells. We found that in vitro culture of PC-3 cells with lutein induced mild decrease in proliferation that improved in combination treatment with peroxisome proliferator-activated receptor gamma (PPARγ) agonists and other chemotherapeutic agents. Flow cytometry analyses showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…However, metastatic breast cancer is heterogeneous and has a high mortality rate due to its inherently aggressive biology. Previous studies have determined that lutein suppresses multiple types of tumor, and the antitumor effects of lutein have been associated with a decline in proliferative signals and growth suppression (21,22,27). Previous studies have focused on the associations between lutein and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, metastatic breast cancer is heterogeneous and has a high mortality rate due to its inherently aggressive biology. Previous studies have determined that lutein suppresses multiple types of tumor, and the antitumor effects of lutein have been associated with a decline in proliferative signals and growth suppression (21,22,27). Previous studies have focused on the associations between lutein and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrated in the retina, lutein decreases the risk of age-associated macular degeneration due to its anti-oxidative properties (19). Previous studies have demonstrated that lutein exhibits potential antitumor properties in several cancers, including cervical carcinoma, colon cancer and hepatic carcinoma (20)(21)(22). Lutein is involved in cancer initiation and progression by regulating cellular redox status and associated signaling pathways.…”
Section: Lutein Inhibits Proliferation Invasion and Migration Of Hypmentioning
confidence: 99%
“…[82] A study performed on 44 men with no previous incidence of any cardiovascular disease showed an inverse correlation between lutein intake and risk for ischemic stroke when followed up for 8 years. [83] Lutein supplementation was also found to have an inverse [84] Supplementation with 10 or 20 mg/d of lutein has proven to be beneficial for cardiovascular diseases in subjects. [85] Cancer prevention…”
Section: Cardiovascular Healthmentioning
confidence: 99%
“…Lutein induced a mild decrease in proliferation, improved PPARγ agonistinduced cell-cycle arrest and apoptosis, and altered the expression of growth and apoptosis-associated biomarker genes. 11 Although these studies suggested the involvement of the PPARγ pathway, they did not investigate PPARγ directly or the contribution of the PPARγ pathway to the inhibition of cancer-cell growth by carotenoids. Recently, our experimental results showed that β-carotene enhanced the expression of PPARγ in breast cancer MCF7 cells.…”
Section: Pparγ Activation In Carotenoidinhibited Cancer-cell Prolifermentioning
confidence: 99%